Inhibition of tyrosine phosphatases induces apoptosis independent from the CD95 system - Hehner, Steffen Peter; Hofmann, Thomas G.; Dröge, Wulf (Cell death and differentiation, 1999)
The inhibition of protein tyrosine phosphatases by pervanadate, a potent activator of B- and T-cells through the induction of tyrosine phosphorylation and downstream signaling events in different activation cascades, efficiently induced apoptosis in lymphoid cell lines. Pervanadate-elicited apoptosis could be blocked by the tyrosine kinase inhibitor herbimycin A. This apoptotic process involved the activation of caspases 3, 8 and 9, the induction of mitochondrial permeability transition, the release of cytochrome C and the fragmentation of chromosomal DNA. T-cells lacking the CD95 receptor or caspase-8 and T-cells stably overexpressing a transdominant negative form of the adaptor protein FADD were still susceptible to pervanadate-induced apoptosis, excluding the involvement of the CD95 system or other FADD-dependent death receptors. The apoptotic program initiated by the inhibition of tyrosine phosphatases did not require the presence of the tyrosine kinase p56lck or phosphatase CD45, whereas Bcl-2 overexpression protected T-cells from pervanadate-induced cytochrome C release, caspase-8 cleavage and apoptosis.
Gesehen am 09.02.2021